1177 SOCIO-DEMOGRAPHIC AND RISK FACTOR DIFFERENCES BETWEEN TIA AND TIA MIMICS. (16th January 2023) - Patel, M; Awatramani, S; Kulendran, A; Umasankar, U
Abstract: Introduction: Diagnosis of Transient Ischaemic Attack [TIA] is important to minimise risk of future strokes. This retrospective descriptive study aimed to evaluate socio-demographic and risk factor differences between TIA and TIA 'mimics' in patients presenting to an inner-city neurovascular clinic. Methods: Data was obtained over a 2-year period [2019-2020] for all new patients assessed in a consultant-provided daily week-day neurovascular service that serves a million multi-ethnic, population. Data collected included socio-demographic details, clinical risk factors, source of referral and final clinical diagnoses. Results: Of 1764 patients, 39% [694] were diagnosed as TIA; 61% [1070] were TIA mimics with 40 distinct differential diagnoses. Compared to TIA mimics, TIA patients were older [mean(SD): 69.3(13.8) vs 59.7(16.1), p<0.001]; higher prevalence of TIA mimics in females vs males [66% vs 54%; p<0.001]. There were proportionately more patients with TIA mimics from Black and minority ethnic groups (401/610:66%) compared whites (669/1154:58%)[p=0.034]. Compared to TIA mimics, TIA patients had higher prevalence of hypertension [56% vs 40%, p<0.001], Diabetes [22% vs 14%, p<0.001], Atrial Fibrillation [10% vs 4%, p<0.001], Chronic Heart Disease [18% vs 9%, p<0.001] and moderate to severe carotid stenosis [5% vs 0.4%, p<0.001]. Prevalence of other risk factors in TIA patients included Patent Foramen Ovale [1.4%], Cardiolipin Antibodies [3.2%], and Thrombophilia [2.3%]. 14% of TIA patients had no identifiable risk factors. Discussion: This large survey has described socio-demographic [age, gender and ethnicity] differences and prevalence of risk factors between TIA patients and TIA mimics. These differences may be useful in terms accurate diagnosis of TIA by experienced clinicians. This study provides valuable information for clinicians and researchers of stroke services in future.